Detection the Virulence Factor (Cytotoxic necrosis factor1) Produce from Uropathogenic Escherichia coli Isolates - H. Hassan, Muthanna; T. Flayih, May; Y. Yaseen, Nahi; A.Suleiman, Ahmed (Iraqi Journal of Science, 2023)
In this study, only four isolates produce CNF1 from 76 isolatesof uropathogenic Escherichia coli.cnf1 gene was detected by using PCR technique, while cytotoxic necrotizing factor 1(CNF1) was determined by Immunoblotting assay.